A simple method to determinate required Rtr values of building envelope components against road traffic noise - Akdag, NY (PERGAMON-ELSEVIER SCIENCE LTD, 2004)
The design of a building should cover necessary investigations to provide comfort conditions, in terms of physical properties such as light, sound and heat. The acoustical comfort conditions in an architectural space significantly depend on the sound insulation performance of the building envelope. The first step in providing a building envelope which will be sufficient in terms of sound insulation, is to select the wall materials having required sound transmission loss values. The aim of this paper is to present a graphic method to determine the required minimum sound reduction index (R-tr) of building envelope components, depending on road traffic noise, room function and transparency ratio of the facade. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: building envelope; road traffic noise; sound insulation; sound reduction index; Construction & Building Technology; Engineering